Electrochemical characterizations and the effect of glycerol in biopolymer electrolytes based on methylcellulose-potato starch blend - Yusof, Y.M.; Kadir, M.F.Z. (Taylor & Francis, 2016)
Polymer electrolytes have been prepared by blending methylcellulose (MC)-potato starch, doped with lithium perchlorate (LiClO4) and plasticized with glycerol. The blend of 60 wt% MC-40 wt% starch was found to be the most suitable ratio to serve as polymer host. Fourier transform infrared (FTIR) spectroscopy analysis proved the interaction among the components. X-ray diffraction (XRD) analysis indicated that the conductivity enhancement is due to the increase in amorphous content. The highest ionic conductivity obtained at room temperature was (4.25 ± 0.82) × 10−4 S cm−1 for MC-starch-LiClO4-20 wt% glycerol. The highest conducting samples in both systems were found to obey Arrhenius rule. Dielectric study further strengthens the conductivity result.